How stereochemistry of lipid components can affect lipid organization and the route of liposome internalization into cells. Issue 27 (2nd July 2021) - Borocci, Stefano; Bozzuto, Giuseppina; Bombelli, Cecilia; Ceccacci, Francesca; Formisano, Giuseppe; Stringaro, Annarita; Molinari, Agnese; Mancini, Giovanna
Abstract : Lipid stereochemistry was shown to drive cell internalization of liposomes through either clathrin or caveolae. Molecular dynamic simulations highlighted molecular interactions that affect physicochemical and biological features of liposomes. Abstract : Though liposome-based drugs are in clinical use, the mechanism of cell internalization of liposomes is yet an object of controversy. The present experimental investigation, carried out on human glioblastoma cells, indicated different internalization routes for two diastereomeric liposomes. Molecular dynamics simulations of the lipid bilayers of the two formulations indicated that the different stereochemistry of a lipid component controls some parameters such as area per lipid molecule and fluidity of lipid membranes, surface potential and water organization at the lipid/water interface, all of which affect the interaction with biomolecules and cell components.